Evaluation of oxidative stress parameters and metabolic activities of nurses working day and night shifts - Turgay Ulas; Hakan Buyukhatipoglu; Idris Kirhan; Mehmet Sinan Dal; Sevilay Ulas; Mehmet Emin Demir; Mehmet Ali Eren; Mehmet Ucar; Abdussamet Hazar; İbrahim Can Kurkcuoglu; Nurten Aksoy (SciELO, 2013)
The aim of this study was to evaluate the oxidative stress and metabolic activities of nurses working day and night shifts. Intensive care unit (ICU) (n=70) and ordinary service (OS) nurses (n=70) were enrolled in the study. Just before and the end of the shifts, blood samples were obtained to measure the participants' oxidative stress parameters. Metabolic activities were analyzed using the SenseWear Armband. Oxidative stress parameters were increased at the end of the shifts for all OS and ICU nurses compared to the beginning of the shifts. Compared to the OS nurses, the ICU nurses' TAS, TOS, and OSI levels were not significantly different at the end of the day and night shifts. The metabolic activities of the OS and ICU nurses were found to be similar. As a result, the OS and ICU nurses' oxidative stress parameters and metabolic activities were not different, and all of the nurses experienced similar effects from both the day and night shifts.